Distal Biceps Tendon Repair: An Arthroscopic-Assisted Technique With Suture Anchors - Enrico Guerra, M.D.; Federico Coliva, M.D.; Catello Buondonno, M.D.; Alessandro Marinelli, M.D. (Arthroscopy Techniques)
Distal biceps tendon ruptures are rare injuries that can lead to significant limitations in forearm supination strength and elbow flexion. Although conservative treatment leads to satisfactory results in many cases, surgical treatment is indicated in high-demanding patients, heavy workers, and athletes. Many different surgical techniques have been described, but the percentage of complications after surgery remains high (almost 25%). The purpose of this article is to describe our preferred surgical approach for acute distal biceps tendon ruptures with an arthroscopic-assisted technique and suture anchor fixation method. We believe that this technique can be easily reproducible and that it might lead to a reduction in the complication rate because it is less invasive.